2019
DOI: 10.1155/2019/1212369
|View full text |Cite
|
Sign up to set email alerts
|

Drugs and Clinical Approaches Targeting the Antiapoptotic Protein: A Review

Abstract: B-cell lymphoma 2 (Bcl-2) is a regulator protein involved in apoptosis. In the past few decades, this protein has been demonstrated to have high efficacy in cancer therapy, and several approaches targeting Bcl-2 have been tested clinically (e.g., oblimersen, ABT-737, ABT-263, obatoclax mesylate, and AT-101). This review reports potential Bcl-2 inhibitors according to current information on their underlying mechanism and the results of clinical trials. In addition, the function and mechanisms of other potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…Such a correlation analysis makes it possible to identify, among already available molecules, those that are adapted to the tumor type according to AhR level. For example, ABT-263 (Navitoclax), which targets the apoptosis inhibitor Bcl-2 [105], was more effective in lung-cancer cell lines that weakly express AhR (left panel of Fig. 4A).…”
Section: Ahr As a Prognostic Marker To Choose The Most Efficient Targmentioning
confidence: 99%
“…Such a correlation analysis makes it possible to identify, among already available molecules, those that are adapted to the tumor type according to AhR level. For example, ABT-263 (Navitoclax), which targets the apoptosis inhibitor Bcl-2 [105], was more effective in lung-cancer cell lines that weakly express AhR (left panel of Fig. 4A).…”
Section: Ahr As a Prognostic Marker To Choose The Most Efficient Targmentioning
confidence: 99%
“…Azmi et al demonstrated that nonpeptidic small-molecule inhibitors of Bcl-2 family proteins (apogossypolone and TW-37) induced Par-4-dependent inhibition of cell growth and induction of apoptosis in pancreatic cancer cells and inhibited tumor growth in xenograft animal model 113 . According to recent data, ~19 different Bcl-2 inhibitors (antibodies, small molecule drugs, and antisense oligonucleotides) are undergoing preclinical or clinical studies for the treatment of different cancers 110 . It will be interesting to evaluate whether some of these agents can induce Par-4.…”
Section: Par-4 In Cancer Therapeutics: Its Brighter On the Other Sidementioning
confidence: 99%
“…29 The follow-up studies demonstrated that gossypol structurally behaves as a BH3-mimetic which can bind to Bcl-2 and Bcl-xl 30,31 and later AT-101 [(-)gossypol] became one of the first orally available Bcl-2 inhibitor that has entered the clinical trials. 32 Up until now, AT-101 has been investigated in more than 20 phase I/II and 1 Phase III clinical trial(s) as a single agent or in combination with other agents against multiple types of cancer (https://clinicaltrials.gov). Two phase II trials are still ongoing in China (CTR20150540, CTR20150541).…”
Section: Gossypol: a Potential Anti-cancer Drug Candidate With A Varimentioning
confidence: 99%